- w+x+y+z=1
- w+x-y-z=7 is the same as 2w+2x-2y-2z=14
- w-2x+2y+z=9
- w-x+7y+5z=-15

Add (1) and (2): 2w+2x=8, that is, w+x=4, **w=4-x**.

Subtract (2) from (1): 2y+2z=-6, that is, y+z=-3, **z=**-3-y=**-(3+y**).

By substituting for w and z in (3):

(4-x)-2x+2y-(3+y)=9 simplifies to **-3x+y=8** (5); and in (4):

(4-x)-x+7y-5(3+y)=-15, 4-2x+7y-15-5y=-15, -2x+2y=-4, -x+y=-2, **y=x-2**.

By substituting for y in (5):

-3x+(x-2)=8, -2x=10, x=-5, and y=-7, w=9, z=4 from other equations in bold print.

- All categories
- Pre-Algebra Answers 12,305
- Algebra 1 Answers 25,233
- Algebra 2 Answers 10,430
- Geometry Answers 5,157
- Trigonometry Answers 2,637
- Calculus Answers 5,997
- Statistics Answers 3,016
- Word Problem Answers 10,085
- Other Math Topics 6,618

81,478 questions

85,655 answers

2,171 comments

69,137 users